Effects of Learning Objects on the Academic Achievement of Students in Web-Based Foreign Language Learning - Basal, Ahmet; Gurol, Mehmet (HACETTEPE UNIV, 2014)
Foreign language education in Turkey has been criticized as being not entirely functional throughout the literature. Implementing effective teaching materials into the foreign language learning environments may serve as a solution to the problem. The aim of this study is to investigate the effects of learning objects (LOs), cutting-edge materials, on the achievement of learners in web-based language learning environments. To this end, this study was conducted in English I Course at the Department of Computer Programming at a Turkish medium state university in 2010-2011 Fall Semester. Seventy LOs appropriate for a six-week long lecture program were integrated into the learning management system (LMS) of the institution. Achievement tests were administered as pre and posttest to the study groups consisted of 118 students and results were analysing using SPSS. The findings indicate that web-based language education supported by LOs has a significant effect on students' achievement scores in the experimental group and LOs can be utilized in language education settings.
Keywords: Learning objects; distance education; web-based distance education; foreign language education; TEACHERS; Education & Educational Research